Leprosy: a review of laboratory and therapeutic aspects - Part 2 - Lastoria, Joel Carlos [UNESP]; Abreu, Marilda Aparecida Milanez Morgado De (Sociedade Brasileira de Dermatologia, 2014)
Leprosy is a chronic infectious condition caused by Mycobacterium leprae(M. leprae). It is endemic in many regions of the world and a public health problem in Brazil. Additionally, it presents a wide spectrum of clinical manifestations, which are dependent on the interaction between M. leprae and host, and are related to the degree of immunity to the bacillus. The diagnosis of this disease is a clinical one. However, in some situations laboratory exams are necessary to confirm the diagnosis of leprosy or classify its clinical form. This article aims to update dermatologists on leprosy, through a review of complementary laboratory techniques that can be employed for the diagnosis of leprosy, including Mitsuda intradermal reaction, skin smear microscopy, histopathology, serology, immunohistochemistry, polymerase chain reaction, imaging tests, electromyography, and blood tests. It also aims to explain standard multidrug therapy regimens, the treatment of reactions and resistant cases, immunotherapy with bacillus Calmette-Guérin (BCG) vaccine and chemoprophylaxis.
Keywords: Clinical evolution; Communicable disease prevention; Diagnosis, differential; Drug resistance; Education, continuing; Laboratory research; Leprosy; Mycobacterium leprae; Prognosis; Therapeutics